Early Detection of Prostate Cancer by Tumour Marker PSA, CEA and CA19.9 - Sahira H. Kareem (Journal of Global Pharma Technology, 2018)
Prostate cancer is the most common cancer and the second leading cause of cancer deaths in men. , tumor markers are substances that can be found in the body when cancer is present, Prostate-specific antigen (PSA) is well known as a specific tumor marker for prostate cancer Carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) elevating adenocarcinomas originating in the prostate gland. In the present study have been investigated the levels of cancer antigen and some of trace element in fifty men, aged were 50 – 75 year they divided into two groups included prostate patients and control groups. This study showed significant increasing (P<0.05) in the level of PSA, CEA and CA19.9 concentration in forty cases of prostate patients and significant increasing (P<0.05) in CEA and CA19.9 concentration with a note that the concentration of PSA was low in ten cases of prostate cancer patients and significant difference in serum trace element concentration.Keywords: Prostate Cancer, PSA, CEA, CA19.9 and Trace Element.